İbn Hurdazbih’in el-Mesâlik ve’l-Memâlik’i ve İçerdiği Coğrafî ve Kültürel Motifler - Ağari, Murat (Dinî araştırmalar, 2005)
Geografie work of İbn Hurradadbih, al-Mamalik and al-Masalik has also cultural and economical value. These invaluable accounts have been helpful for midle-East historians. These accounts can be essentially divided into three chapters:-Geographic accounts -Cultural Accounts -Economical Accounts By the means of these precious information, to study Middle-East history has been not only amusing but also easy